Brazing ZrB2-SiC ceramics to Ti6Al4V alloy with TiCu-based amorphous filler. (December 2017) - Liu, Yaping; Wang, Gang; Cao, Wei; Xu, Haitao; Huang, Zhongjia; Zhu, Dongdong; Tan, Caiwang
Graphical abstract: Highlights: ZrB2 -SiC ceramic and TC4 alloy joint was brazed using TiCu-based amorphous filler. Formation mechanism of the joint was discussed in detail. Shear strength depends on the eutectic structure and brittle compounds in the joint. Abstract: In this work, the Ti-6Al-4V alloy and ZrB2 -SiC ultra-high temperature ceramic joint was brazed by TiCuZrNi amorphous filler at 910 °C with varied holding time. The element diffusion, microstructure and precipitation phase of the joints were analyzed in details. Reaction products in the joints were identified as β -Ti, (Ti, Zr)2 (Cu, Ni), TiCu, Ti2 Cu, TiC, Ti5 Si3, TiB and TiB2. The formation schemes of reaction products were investigated. The holding time has substantial impacts on interfacial microstructure and shear strength of joints. A maximum shear strength of 345 MPa of the joint was reached under a brazing temperature of 910 °C and holding time of 1200 s. It is also found that the shear strength depends on the amount of eutectic structure and brittle compounds in the joints.